Personal care and practical support at home: a systematic review of older people's views and experiences. Issue 2 (10th June 2019) - Kwan, Irene; Rutter, Deborah; Anderson, Beth; Stansfield, Claire
Abstract : Purpose: Considering the views of service users is important to identify their needs as this helps providers to develop appropriate and responsive services. For older people receiving home care, recognising their needs is the first step towards supporting them to maintain independence and promote wellbeing. The paper aims to discuss these issues. Design/methodology/approach: A systematic review was conducted in 2014 to explore the personal experiences of older people in England about the care and support they received at home. Studies published between 2004 and 2013 were identified from bibliographic databases and websites. A total of 17 studies satisfied the inclusion criteria. Data were extracted using a standardised coding tool and narratively synthesised. Study quality was evaluated. Findings: Nine themes were identified. Older people valued an approach that was person centred, flexible and proactive to respond to their changing needs and priorities, focusing on what they can or would like to do to maintain their independence. Allowing time to build trust between older people and their care workers helped to realise older peoples' aspirations and goals. Practical help to promote choice and reduce social isolation was perceived to be as important as personal care. Practical implications: Evidence from this review contributed to the development of a social care guideline on home care, and informed key practice recommendations for care providers in England. Originality/value: This review highlighted the value older people place in person-centred care incorporating practical help both inside and outside the realm of personal care.